Planet Earth or Planet Desert? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
There are many causes for degradation, including bushfires, over-exploitation of forests, intense drought. But, equally, there are many ways of reducing the gradual desertification of the planet by restoring riverbanks, managing soil in a sustainable